The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.4034/1519.0501.2009.0091.0002
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion and Orthodontic Treatment Need of Mentally Handicapped Children in Lagos, Nigeria

Abstract: RESUMOObjetivo: Determinar a prevalência de maloclusão e necessidade de tratamento ortodôntico em crianças e adolescentes nigerianos com necessidades especiais através do Dental Aesthetic Index (DAI); e avaliar se a maloclusão sofre influência da idade e do sexo da criança. Método: A amostra foi composta por 102 crianças e adolescentes com idades entre 6 a 18 anos atendidos em 5 escolas/centros para pessoas com necessidades especiais. Um questionário pré-estruturadp foi utilizado para coletar dados sócio-demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 15 publications
2
15
2
2
Order By: Relevance
“…Nevertheless, the observed difference in the prevalence is not so marked. Considering the space anomalies, the prevalence of crowding in incisal segment (58.8%) reported by the current study is similar to that which was reported in Nigeria [52] in an identical group of disabilities. However, there was a considerable difference in the prevalence of spacing in incisal segment between the current and the one which was reported in Nigeria [25], this might be attributed to the difference in indices used in scoring malocclusion.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Nevertheless, the observed difference in the prevalence is not so marked. Considering the space anomalies, the prevalence of crowding in incisal segment (58.8%) reported by the current study is similar to that which was reported in Nigeria [52] in an identical group of disabilities. However, there was a considerable difference in the prevalence of spacing in incisal segment between the current and the one which was reported in Nigeria [25], this might be attributed to the difference in indices used in scoring malocclusion.…”
Section: Discussionsupporting
confidence: 78%
“…The study observed Class I molar relationship of about 75% among children with neuropsychological disabilities, this is in contrast to that reported by Utomi et al, [52] who found slightly lower prevalence of Class I molar relationship (68.6%) in similar group of disabilities. Nevertheless, the observed difference in the prevalence is not so marked.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In literature, authors like Utomi et al [1] found the need for orthodontic care in 68% of patients in a university hospital center in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment decision must be based on objective criteria [1] [2]. Thus, accurately assessing the care needed is an approach that must be duplicable, irrespective of the practitioner together with a universal language accessible to all stakeholders (practitioner, patients, insurance, health mutual).…”
Section: Introductionmentioning
confidence: 99%